Valorización económica de los residuos sólidos inorgánicos domiciliarios, parroquia Shushufindi Central, cantón Shushufindi, provincia de Sucumbíos. - Tenorio Mina, Pahola Noemi (2016)
This study entitled "Economic Valuation of Solid Waste Inorganic Domiciliary of Shushufindi Central Parish Shushufindi Canton province of Sucumbíos". It was determined that the total production of solid waste in the central Shushufindi parish is 25.383,50 kg / day and per capita production of 0,79 kg / person / day. Based on the total production of household solid waste, by the method of quartering physical composition thereof was determined and the amount of solid waste potentially recyclable in the parish Shushufindi which are represented by paper, cardboard, glass, plastic was determined PET, hard plastic that could be used and these together represent 15.30% of the total waste produced in the parish (3.883,70 kg / day). With these data we proceeded to give an economic value to each of these waste by a market study and establishing an economic value that is the same as the recycling companies parish, setting a value of 514,80 USD/ day. This research was directed to establish a quantitative economic value to recyclable household waste of Shushufindi Central Parish. Keyword: Solid Wastes Recyclable, Carted method, Base Line.